Predatory bacteria can intensify lung-injury in a multidrug-resistant Acinetobacter baumannii pneumonia model in rat - Mohsenipour, Zeinab; Kianian, Farzaneh; Jahanbin, Behnaz; Abtahi, Hamid Reza; Ghazanfari, Tooba; Edalatifard, Maryam; Amanpour, Saeid; Skurnik, Mikael; Arazi, Parya; Feizabadi, Mohammad Mehdi (Frontiers in Microbiology, 2025)
IntroductionRespiratory tract infection caused by antibiotic-resistant bacteria are one of the most important causes of death worldwide. Therefore, in this study, we investigated the possibility of using predatory bacteria to improve the Acinetobacter baumannii pneumonia model in rat.MethodsMultidrug-resistant (MDR) A. baumannii clinical strain was used to induce pneumonia. In addition to the sham and predator control group, three treatment groups (n = 5) were studied with colistin, Bdellovibrio bacteriovorus HD100, and combination of predator and antibiotics. Also, the colistin MIC value for B. bacteriovorus HD100 (8 μg/mL) was determined for the first time to our knowledge. Removal of excess endotoxin from the predator suspension was performed with the help of organic solvents before inoculation of rats.ResultsThe most successful treatment was observed in the group treated with colistin followed by combined treatment. In the predator treatment group, the systemic spread of A. baumannii was lower than other treatment groups. However, treatment with predatory bacteria not only failed to reduce the pathogen load in the lungs to the same extent as the antibiotic treatment group, but also induced acute pulmonary and systemic inflammatory responses. Therefore, the rats showed the highest septic score (21.4 at 48 h) and did not survive more than 48 h.DiscussionThis is the first report of systemic complications of using B. bacteriovorus HD100 for infection control. According to our results, the effects of predatory bacteria in the in vivo environment are complex and many questions need to be answered before it can be introduced as a live antibiotic.